Evaluation analysis of the rodanya masbagia program in Magelang city: review of effectiveness and impact - Orbawati, Eny Boedi; Wismaningtyas, Tri Asih; Fadlurrahman, Fadlurrahman; Mukti, Ari (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study evaluates the effectiveness of the Advanced Healthy and Happy Community Empowerment Program (Rodanya Masbagia) in Magelang City, which aims to improve community welfare through active participation in the planning of local activities supported by the annual budget. In its implementation, this program faces obstacles such as limited understanding from several RT Heads and Community Groups (Pokmas) regarding program procedures and rules. This study uses six dimensions of policy evaluation, namely effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy. The research method is in the form of a quantitative survey with a sample of beneficiaries and members of the implementing organization. Data were collected through questionnaires and analyzed with a Likert scale to assess the effectiveness of the program. The purposive sampling technique is used for informants from program implementers, while cluster sampling is applied to communities in various sub-districts. The results showed that most of the evaluation dimensions, such as effectiveness, adequacy, and equity, were in the high category. However, there are still several aspects that need to be improved, such as public understanding in preparing Community Activity Plans (RKM), obstacles in accountability reports, and coordination between parties. The efficiency of the operational budget is also considered not fully adequate. In conclusion, the Masbagia Wheel Program has been quite effective and beneficial to the community, but challenges in technical implementation still need to be overcome. Recommendations include more intensive socialization, capacity building in the preparation of RKM and financial statements, and better coordination between related parties. This research is expected to be a reference for local governments to improve the quality of programs in the future.